Abrupt introduction of distance learning during the covid‑19 pandemic: What psychological impact on teachers? - Hanane Aissaoui; Mariam Atassi; Asmae Lekfif; Mohammed A. Bouazzaoui; Asmae Yeznasni; Sanae Sabbar; Naima Abda (AOSIS, 2023)
As soon as the COVID‑19 pandemic appeared, the Moroccan education ministry decided to adopt distance learning (DL). Our target was to study the psychological impact of DL on Moroccan teachers during the pandemic. This cross‑sectional study used an online questionnaire based on the Hospital Anxiety and Depression Scale. Among 148 responses, 64.9% were women, and the average age was 41.1±11.5 years. 79.1% participated in DL, 58.8% were required to acquire DL tools and 71.6% had never received DL training. Between the start and the end of confinement, we noticed a decrease in the motivation of teachers.36.2% had definite depressive symptomatology and 41.3% had certain anxiety symptomatology with a significant predominance in women. The frequencies of depression and anxiety were higher in those who had participated in DL, but the association was not significant. Depression was significantly frequent among teachers who were obliged to acquire tools to practice DL P=0.02, those who had never received training DL P=0.046, and those who were not satisfied with the situation P=0.03. We didn't find a direct association between DL and anxiety and depression, which the small sample size may explain, but we did find an association with the variables related to DL.